2004
DOI: 10.5194/hess-8-706-2004
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for predicting soil temperature in snow-covered and seasonally frozen soil: model description and testing

Abstract: Microbial processes in soil are moisture, nutrient and temperature dependent and, consequently, accurate calculation of soil temperature is important for modelling nitrogen processes. Microbial activity in soil occurs even at sub-zero temperatures so that, in northern latitudes, a method to calculate soil temperature under snow cover and in frozen soils is required. This paper describes a new and simple model to calculate daily values for soil temperature at various depths in both frozen and unfrozen soils. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 9 publications
3
99
0
Order By: Relevance
“…McCann et al, 1991) and only a few consider the effect of snow cover on heat transfer (e.g. Rankinen et al, 2004). A sinusoidal function of time oscillating around an average value with an increasing phase shift and attenuation with depth is often used to describe large-scale soil temperature dynamics (Campbell, 1985), and seems to work well also at the field scale in warm temperate climates, if surface temperature is known (Wu & Nofziger, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCann et al, 1991) and only a few consider the effect of snow cover on heat transfer (e.g. Rankinen et al, 2004). A sinusoidal function of time oscillating around an average value with an increasing phase shift and attenuation with depth is often used to describe large-scale soil temperature dynamics (Campbell, 1985), and seems to work well also at the field scale in warm temperate climates, if surface temperature is known (Wu & Nofziger, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…4 A number of empirical or semi-empirical soil temperature models have been proposed (e.g. Gupta et al, 1982;McCann et al, 1991;Paul et al, 2004;Rankinen et al, 2004;Bond-Lamberty et al, 2005 and papers cited therein). Many of these models are not sensitive to surface cover (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Rankinen et al (2004) soil temperature model incorporated in INCA-C was adequate for all seasons except winter. Given the importance of winter soil temperature for soil and streamwater [DOC] in the following spring Å gren et al 2010), this is a potentially serious shortcoming.…”
Section: Discussionmentioning
confidence: 99%
“…All process rates are dependent on modeled soil temperature and moisture (Futter et al 2007). Soil temperature is modeled from air temperature using a relationship developed by Rankinen et al (2004) in which soil temperature is controlled by air temperature, insulating effects of snow cover, a soil thermal conductivity coefficient, heat capacity due to freeze/thaw and modeled soil temperature on the preceding day.…”
Section: Inca-c Modelmentioning
confidence: 99%
“…Bond-Lamberty et al (2005) showed the relative importance of incorporating changes in forest canopy and leaf area index in improving soil temperature simulations. Recent work by Jungqvist et al (2014) assessed possible future change in upland forest soil temperature dynamics by extending the model of Rankinen et al (2004). However, simple models are evolving into models of varying complexities as the need to assess the impact of climate change on soil temperature becomes important in soil biogeochemistry (Kurylyk et al 2013).…”
Section: Introductionmentioning
confidence: 99%